Dietary Antioxidant Supplementation Promotes Growth in Senegalese Sole Postlarvae - Xavier, Maria J.; Engrola, Sofia; Conceição, Luis E. C.; Manchado, Manuel; Carballo, Carlos; Gonçalves, Renata; Colen, Rita; Figueiredo, Vera; Valente, Luisa M. P. (Frontiers in Physiology, 2020)
Somatic growth is a balance between protein synthesis and degradation, and it is largely influenced by nutritional clues. Antioxidants levels play a key role in protein turnover by reducing the oxidative damage in the skeletal muscle, and hence promoting growth performance in the long-term. In the present study, Senegalese sole postlarvae (45 days after hatching, DAH) were fed with three experimental diets, a control (CTRL) and two supplemented with natural antioxidants: curcumin (CC) and grape seed (GS). Trial spanned for 25 days and growth performance, muscle cellularity and the expression of muscle growth related genes were assessed at the end of the experiment (70 DAH). The diets CC and GS significantly improved growth performance of fish compared to the CTRL diet. This enhanced growth was associated with larger muscle cross sectional area, with fish fed CC being significantly different from those fed the CTRL. Sole fed the CC diet had the highest number of muscle fibres, indicating that this diet promoted muscle hyperplastic growth. Although the mean fibre diameter did not differ significantly amongst treatments, the proportion of large-sized fibres (>25 µm) was also higher in fish fed the CC diet suggesting increased hypertrophic growth. Such differences in the phenotype were associated with a significant up-regulation of the myogenic differentiation 2 (myod2) and the myomaker (mymk) transcripts involved in myocyte differentiation and fusion, respectively, during larval development. The inclusion of grape seed extract (GS diet) resulted in a significant increase in the expression of myostatin1. These results demonstrate that both diets (CC and GS) can positively modulate muscle development and promote growth in sole postlarvae. This effect is more prominent in CC fed fish, where increased hyperplastic and hypertrophic growth of the muscle was associated with an upregulation of myod2 and mymk genes.